The Preparedness of a Philippine Higher Education Institution on the Implementation of Flexible Learning (FL) - Absolor , Jocelyn L.; Morla, Enhelyn L.; Villanueva, Gina Mae C.; Yacap, Marites J.; Bueno, Jerome R. (Technium Social Sciences Journal, 2022)
HEIs’ response and innovations for the continuity of quality education during pandemic were the biggest challenges beset by them.This study mainly assessed the preparedness of Ilocos Sur Polytechnic State College, Philippines on the implementation of flexible learning amidst COVID 19 pandemic. The areas considered along preparedness are the following: resources, modes of delivering instructions, policies, support services for students, course packages(available offline/online), mechanisms for students to receive and access printed or digital course packages and instructional materials and establishment/availability/utilization of multi-media or learning resource center/s for faculty members. This study further determined the constraints on the implementation of flexible learning and results served as a benchmark in the development of a Learning Continuity Plan(LCP). This study made use of a descriptive design with 137 faculty respondents selected randomly. A survey questionnaire was used to gather data. Results reveal that the college is at the average level of preparedness.Resources, modes of delivering instruction,policies, courier, electronic library and Learning Management System(LMS) were identified as constraints that need to be improved.The Learning Continuity Plan(LCP) suggested measures to improve the implementation of Flexible Learning(FL).With these results,it is suggested that resources,Learning Management System(LMS),policies and modes of delivering instruction shall be established systematically.